ԺԳ դարում ընդօրինակված «Բանք իմաստասիրաց»-ի չորս տարբեր բնագիր - Պողոսյան, Ռուզան
More than a hundred copies of “Sayings of Philosophers” (Բանք իմաստասիրաց) in the handwritten Miscellanies belonging to the 13th-19th centuries are kept at the Matenadaran. Тhey have been studied by Emilio Teza, Jakobus Dashian, Knarik Ter-Davtyan, and others, but the critical edition still remains unaccomplished. This paper is an attempt to discuss the striking peculiarities of those copies as well as to emphasize the diversity in their content and structure by comparing them with the printed recension published in the first volume of “Sop‘erk‘ haykakank‘” in 1853. It is devoted to four copies of “Sayings of Philosophers” in the earliest 13th century Miscellanies. В рукописных “Сборниках” XIII-XIX вв., хранящихся в Матенадаране, насчитывается более сотни экземпляров “Изречений философов” (Բանք իմաստասիրաց). Их изучали арменоведы Эмилио Теза, Акобос Ташян, Кнарик Тер-Давтян и другие, но научное издание до сих пор остается незавершенным. В данной статье делается попытка рассмотреть особенности этих рукописей, а также подчеркнуть несхожесть их содержания и структуры путем сравнения их с печатной версией, опубликованной в первом томе “Армянских сочинений” (Սոփերք հայկականք) в 1853. В статье представлены четыре версии “Изречений философов” в самых ранних рукописных сборниках, дошедших до нас с XIII в.
Keywords: Բանասիրություն